Analysis of Migrant Compounds from Food Packaging: Application to Disposable Tableware and Risk Analysis - Jiménez Estremera, Carlos; Blázquez-Martín, Javier; Domeño Recalde, Celia; Nerín de la Puerta, Cristina (Jornada de Jóvenes Investigadores del I3A, 2024)
Substance migration from nine types of disposable plates made from cardboard, polystyrene (PS), and polypropylene (PP) have been studied. Migration tests were performed in four food simulants over 10 days at 40°C. Simulant extracts were analyzed using SPME-GC-MS and UPLC-QTOF-MS to identify and (semi)quantify volatile and non-volatile migrants, respectively.